La ficha CAS como instrumento de asignación de subsidios - Ministerio de Planificación y Cooperación. Chile (Documentos/Sociales ;, 1990)
Normas contenidas: V.1 NCH2959OF2006, NCH3013OF2006, NCH2982OF2006, NCH2967OF2005, NCH2973OF2006.V.2: NCH2984OF2006, NCH2986OF2006, NCH2987/1, NCH2987/2.V.3: NCH2990/1, NCH2990/2, NCH2990/3, NCH2990/4, NCH2990/5, NCH2990/6, NCH2990/7, V.4:NCH2966OF2005, NCH2968OF2006